(untitled) (Research, Society and Development, 2022)
Introduction: Numerous studies have evaluated the incidence of the middle-mesial canal in the mesial root of mandibular first molars. However, the available data is varied due to numerous factors related to study methodologies.Aim: To evaluate the incidence of the middle-mesial canal in mandibular first molars through tomographic image analysis. Methodology: A sample of 81 tomographic images of 133 mandibular first molars (acquired with the Orthopantomograph OP300 and the OnDemand 3D Dental system), were observed in mandibular axial section to investigate the presence of the middle-mesial canal and its anatomical configuration. Results: The incidence rate of the middle-mesial canal was 23.30% in the included samples. According to Vertucci’s classification: 66.6% type II; 3.33% type VI; and 30% type VIII. According to Versiani et al., 30% ended in an independent foramen, 3.33% in four independent conduits, and 66.6% with confluence for the mesiobuccal or mesiolingual canals. Conclusion: The incidence of the middle-mesial canal corresponded to 23.30% of the total sample as evaluated by tomographic analysis.